Kinetics of substrate utilization and bacterial growth of crude oil degraded by Pseudomonas aeruginosa - Talaiekhozani, Amirreza (Biomed Central LTD, 2015)
Pollution associated with crude oil (CO) extraction degrades the quality of waters, threatens drinking water sources and may ham air quality. The systems biology approach aims at learning the kinetics of substrate utilization and bacterial growth for a biological process for which very limited knowledge is available. This study uses the Pseudomonas aeruginosa to degrade CO and determines the kinetic parameters of substrate utilization and bacterial growth modeled from a completely mixed batch reactor. The ability of Pseudomonas aeruginosa can remove 91 % of the total petroleum hydrocarbons and 83 % of the aromatic compounds from oily environment. The value k of 9.31 g of substrate g-1 of microorganism d-1 could be far higher than the value k obtained for petrochemical wastewater treatment and that for municipal wastewater treatment. The production of new cells of using CO as the sole carbon and energy source can exceed 23 of the existing cells per day. The kinetic parameters are verified to contribute to improving the biological removal of CO from oily environment